2021
DOI: 10.1007/s10212-021-00536-2
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional profiles of learning orientations and school achievement: a person-oriented approach in middle-school students

Abstract: A person-oriented approach was applied to the study of early adolescents’ learning orientations to identify different profiles and their association with school achievement. A total of 244 middle-school students (male: 128; female: 116; M-age ± SD = 12.51 ± .93) completed a self-report questionnaire to explore cognitive, metacognitive, and affective dimensions of learning orientations. School achievements were collected in a range of school subjects. Cluster analyses and one-way MANOVA were carried out to veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 53 publications
4
8
0
Order By: Relevance
“…A general consensus derived from SoLT suggests that different teaching methods work better for certain populations, with learning patterns as an important intervening factor (Vermunt and Donche, 2017). Moreover, researchers have shown learning patterns and their influence on academic performance to be highly context-dependent (Vettori et al. , 2021; Umapathy et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A general consensus derived from SoLT suggests that different teaching methods work better for certain populations, with learning patterns as an important intervening factor (Vermunt and Donche, 2017). Moreover, researchers have shown learning patterns and their influence on academic performance to be highly context-dependent (Vettori et al. , 2021; Umapathy et al.…”
Section: Discussionmentioning
confidence: 99%
“…A general consensus derived from SoLT suggests that different teaching methods work better for certain populations, with learning patterns as an important intervening factor (Vermunt and Donche, 2017). Moreover, researchers have shown learning patterns and their influence on academic performance to be highly context-dependent (Vettori et al, 2021;Umapathy et al, 2020), which suggests the relevance of their analysis in the EE context. In fact, Rideout and Gray (2013) concluded that different EE interventions work better for certain populations, but this is just speculation and more quantitative research is needed to prove their claim.…”
Section: Students' Learning Patternsmentioning
confidence: 99%
See 3 more Smart Citations